The impact of academic integrity of higher education quality - Andrieieva, Vita; Андрєєва, Віта Анатоліївна (Scientific Center of Innovative Researches OÜ, 2020)
In 2016, the Strengthening Academic Integrity in Ukraine Project (SAIUP) was launched in Ukraine, to which they joined jointly with the Ministry of Education and Science of Ukraine, with the support of the United States Embassy, 10 Ukrainian universities, which have different geographies, vary in number of students or specialization. Dishonesty in education has a negative impact on the entire society creates a system where success cannot be achieved fairly, and such a society cannot be successful in the long run
Keywords: academic integrity; educational environment; higher education; learning process; transparency